Association between adolescent motherhood and maternal and child health indices in Maiduguri, Nigeria: a community-based cross-sectional study. Issue 3 (8th March 2019) - Oyeyemi, Adewale L; Aliyu, Salamatu U; Sa'ad, Fatima; Rufa'i, Adamu Ahmad; Jajere, Abdul Rahman M; Oyeyemi, Adetoyeje Y
Abstract : Introduction: Adolescent motherhood (childbearing below 18 years of age) is a major global health and social problem. Understanding the impact of early motherhood on maternal and child health indices is important to community and population health promotion in developing countries. This study examined the association between adolescent motherhood and maternal and child health indices in Maiduguri, Nigeria. Methods: A cross-sectional design method was used to recruit 220 mothers (age=14–25 years) from four communities in the city of Maiduguri, Northeastern Nigeria. Participants were surveyed using a self-developed interviewer-administered questionnaire that assesses maternal and child health indices and sociodemographic characteristics. Logistic regression analysis was used to compute adjusted OR and 95% CI of the associations between motherhood in adolescence (mothers below 18 years old) and maternal and child health indices. Results: Compared to adult mothers, adolescent mothers were more likely to experience fistula (OR=5.01, 95% CI=3.01 to 14.27), to have postpartum haemorrhage (OR=6.83, 95% CI=2.93 to 15.92), to have sexually transmitted infections (OR=6.29, 95% CI=2.26 to 17.51) and to lose a child within 5 years of birth (OR=3.52, 95% CI=1.07 to 11.60). Children born to adolescent mothers were less likely to have normal weight at birth (OR=0.34, CI=0.15 to 0.73) than those born to adult mothers. Conclusion: Adolescent motherhood was associated with negative maternal and child health indices. The findings can be used by public health professionals including physiotherapists in this role to inform effective primary healthcare practice and community health advocacy to improve maternal and child health indices among adolescent mothers in Maiduguri. Future studies are needed to confirm the evidence at the regional or national level including the rural population in Nigeria.